MIKROALBUMINURIA SEBAGAI PREDIKTOR LUARAN BURUK STROKE ISKEMIK AKUT DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - Hesti Heptaningrum,* I Made Oka Adnyana,* Thomas Eko Purwata,* (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION MICROALBUMINURIA IS ONE OF INDICATORS FOR SYSTEMIC ENDOVASCULAR DAMAGE RELATED TO ENDOTHELIAL DAMAGE AND DYSFUNCTION MICROALBUMINURIA HAS BECOME AN IMPORTANT RISK FACTOR FOR PREDICTING THE RISK AND PROGNOSIS OF CEREBROVASCULAR DISEASE HOWEVER ITS ASSOCIATION WITH ACUTE ISCHEMIC STROKE REMAINS UNCLEAR PARTICULARLY THOSE RELATED WITH OTHER COMORBIDITIES